Pine nut shells of Siberian cedar as a resource for the high-strength smokeless fuel - Tabakaev R. B. Roman Borisovich; Ibraeva K. T. Kanipa Talgatovna; Astafjev A. V. Aleksandr Vladimirovich; Dubinin Yu. L. Yury Lvovich; Altynbaeva D. B. Dariga Bakhitzhanovna; Larionov K. B. Kirill Borisovich; Yankovsky S. A. Stanislav Aleksandrovich; Yazykov N. Nikolay (2024, 2024)
Title screen